Foamed magnesium composite filler as well as preparation method and application thereof
By using foam magnesium composite filler as an electronic donor for autotrophic denitrification, the problem of high cost and easy flow of nitrate sewage denitrification process in existing sewage treatment technologies is solved, and efficient and economical nitrification effect is achieved.
Patent Information
- Application Number
- CN202311226043.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-03-21
AI Technical Summary
Among the existing sewage treatment technologies, the denitrification process of nitrate sewage has the problems of high cost, easy flow or mineralization, and unsatisfactory nitrification treatment.
Foamed magnesium composite filler is used as the electron donor for autotrophic denitrification. The nitrate nitrogen in the wastewater is converted into nitrogen through the reaction of magnesium and hydrogen. The filler is a porous foam structure, including magnesium, foaming agent residue and an inorganic carbon source, and is prepared by hot extrusion and melt foaming.
The transportation and storage costs of sewage treatment are reduced, mudification and mineralization are avoided, denitrification efficiency is improved, and the cost is about 0.75 times that of solid solid iron-based fillers, and the treatment efficiency can reach more than 5 times that of iron-based fillers.
Smart Images

Figure CN119660953A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sewage treatment, and more specifically to a foam magnesium composite filler and a preparation method and application thereof. Background Art
[0002] Nitrate pollution is one of the most important water quality problems nowadays, and the treatment of nitrate in sewage is imminent. The current mainstream method for removing nitrate is heterotrophic denitrification. Heterotrophic denitrification requires sufficient organic carbon sources in the water. If the C / N ratio of sewage is low, the organic carbon source of conventional heterotrophic denitrification is insufficient, which will make it difficult for the total nitrogen in the effluent to meet the discharge standards. The total nitrogen in the effluent mainly exists in the form of nitrate nitrogen, which hinders the regeneration and reuse of sewage. If the problem of insufficient organic carbon source is solved by adding an external organic carbon source, the raw material cost of sewage treatment will be greatly increased, and the high sludge output will also increase the cost of residual sludge treatment. Therefore, it is necessary to explore a more energy-saving and efficient denitrification process.
[0003] Autotrophic denitrification can overcome the problems of heterotrophic denitrification mentioned above. At present, the electron donors of autotrophic denitrification mainly include hydrogen, sulfur, iron and its related compounds such as ferrous sulfide compounds and thiosulfate. Among them, hydrogen is expensive and not suitable for storage and transportation; sulfur and sulfide will produce a large amount of sulfate, and will cause pipeline blockage and ditch flow; iron and its ferrous sulfide compounds have low denitrification efficiency and serious mineralization problems.
[0004] It can be seen that it is of great significance to develop a new electron donor for autotrophic denitrification as a wastewater treatment filler to reduce transportation and storage costs, reduce or avoid mudification and mineralization, and have a more efficient denitrification efficiency. Summary of the invention
[0005] The purpose of the present invention is to provide a foam magnesium composite filler and a preparation method and application thereof, so as to solve the technical problems in the prior art that the filler used in nitrate wastewater treatment is high in cost, easy to channel or mineralize, and the nitrate-nitrogen treatment effect is not ideal.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] In a first aspect, the present invention provides a foamed magnesium composite filler, comprising magnesium, a foaming agent residue and an optional inorganic carbon source, and having a porous foam structure.
[0008] The foamed magnesium composite filler provided by the present invention is applied to sewage treatment, and the autotrophic denitrifying bacteria use the magnesium in the foamed magnesium composite filler and the hydrogen generated by magnesium in water as electron donors to convert the nitrate nitrogen in the sewage into nitrogen. The specific reaction process is as follows:
[0009] 5Mg+2NO3 -+6H2O→5Mg 2+ +N2+12OH -
[0010] Mg+H2O→H2+Mg(OH)2
[0011] 5H2+2NO3 - →N2+2OH - +4H2O
[0012] The foam magnesium composite filler provided by the present invention is a material with a porous foam structure, which can enable autotrophic denitrifying bacteria to grow in large quantities on the surface of the porous foam material and form a biofilm, and synergistically treat nitrate in water through an autotrophic denitrification process using magnesium and hydrogen as electron donors.
[0013] According to some embodiments of the present invention, the density of the foamed magnesium composite filler is 0.8 to 1.2 g / cm 3 .
[0014] According to some embodiments of the present invention, the foamed magnesium composite filler preferably has particles with a particle size of 8 to 13 mm.
[0015] According to some embodiments of the present invention, the mass ratio of magnesium, foaming agent residue and inorganic carbon source is (70-80): (6.5-13): (0-15).
[0016] According to some embodiments of the invention, the blowing agent residue comprises sodium carbonate.
[0017] In the present invention, the foaming agent residue is sodium carbonate generated after the foaming agent sodium bicarbonate decomposes to generate gas. Sodium carbonate can be used as an inorganic carbon source. Therefore, the foaming agent residue can also substantially play the role of an inorganic carbon source.
[0018] According to some embodiments of the present invention, the inorganic carbon source includes at least one of sodium carbonate, calcium carbonate, magnesium carbonate, zinc carbonate, and ferrous carbonate.
[0019] In a second aspect, the present invention provides a method for preparing the foamed magnesium composite filler described in the first aspect, comprising: mixing magnesium powder, a foaming agent and an optional inorganic carbon source raw material to obtain a mixture, first pressing the mixture by hot extrusion, then heating to decompose the foaming agent to generate gas to expand the mixture, cooling and solidifying to obtain the foamed magnesium composite filler.
[0020] The invention adopts a hot extrusion melting foaming method to prepare the foamed magnesium composite filler.
[0021] According to some embodiments of the present invention, the mixture is pressed into a dense semi-solid state by hot extrusion.
[0022] According to some embodiments of the present invention, the mass ratio of the magnesium powder, the foaming agent and the inorganic carbon source raw material is (70-80): (10-20): (0-15).
[0023] According to some embodiments of the invention, the foaming agent is sodium bicarbonate.
[0024] In the invention, sodium bicarbonate is used as a foaming agent, which can not only generate gas through the decomposition of sodium bicarbonate to form a porous foam structure, but also the sodium carbonate generated after the decomposition and foaming of sodium bicarbonate can also be used as an inorganic carbon source.
[0025] According to some embodiments of the present invention, the inorganic carbon source raw material includes at least one of sodium carbonate, calcium carbonate, magnesium carbonate, zinc carbonate, and ferrous carbonate.
[0026] According to some embodiments of the present invention, the particle size of the magnesium powder is 50 to 200 μm.
[0027] According to some embodiments of the present invention, the particle size of the foaming agent is 50 to 200 μm.
[0028] According to some embodiments of the present invention, the particle size of the inorganic carbon source raw material is 50 to 200 μm.
[0029] According to some embodiments of the present invention, the temperature of the hot extrusion is 90-120° C., the pressure is 270-350 MPa, and the holding time is 2-5 hours.
[0030] According to some embodiments of the present invention, the heating temperature is 680-690° C., the purpose of which is to completely melt the magnesium and completely decompose the sodium bicarbonate into sodium carbonate and carbon dioxide.
[0031] According to some embodiments of the present invention, the density of the mixture after expansion is 0.8 to 1.2 g / cm 3 The purpose is to make the foam magnesium composite filler suspended in the water without floating on the surface or sinking to the bottom of the reactor.
[0032] According to some embodiments of the present invention, the preparation method further comprises: cutting the prepared foamed magnesium composite filler into particles, preferably particles with a particle size of 8 to 13 mm.
[0033] In a third aspect, the present invention provides an autotrophic denitrification reactor, comprising the foamed magnesium composite filler described in the first aspect or the foamed magnesium composite filler prepared by the preparation method described in the second aspect.
[0034] According to some embodiments of the present invention, the foamed magnesium composite filler accounts for 45-70% of the volume of the reactor.
[0035] According to some embodiments of the present invention, autotrophic denitrifying bacteria that use magnesium and hydrogen as electron donors are selected as the dominant bacteria in the reactor.
[0036] In a fourth aspect, the present invention provides use of the foamed magnesium composite filler described in the first aspect, the foamed magnesium composite filler prepared by the preparation method described in the second aspect, or the reactor described in the third aspect in sewage treatment.
[0037] According to some embodiments of the present invention, the application is in treating sewage with a dissolved oxygen concentration of 0.5-2.0 mg / L and a ratio of COD concentration to nitrate nitrogen concentration (C / N) less than 3.
[0038] The beneficial effects of the present invention are at least:
[0039] (1) The raw material components of the foam magnesium composite filler provided by the present invention are simple, and the production, transportation and storage costs are much lower than those of hydrogen autotrophic denitrification fillers.
[0040] (2) The magnesium contained in the magnesium foam composite filler provided by the present invention and the small amount of hydrogen generated by magnesium in water together serve as electron donors for autotrophic denitrification. There are more types of autotrophic denitrifying bacteria in the system and the bacterial community is more stable, so that the denitrification effect of the magnesium foam composite filler on nitrate-containing wastewater is also more stable.
[0041] (3) The magnesium foam composite filler provided by the present invention does not have the problem of filler mudding, and will not cause channeling, pipeline clogging and the like.
[0042] (4) Magnesium has stronger reducing properties than iron. The efficiency of the foamed magnesium composite filler provided by the present invention in treating nitrate-containing wastewater is higher than that of iron autotrophic denitrification. Under the same volume, the cost of the foamed magnesium composite filler provided by the present invention is about 0.75 times that of the solid iron-based filler, and the reduction efficiency can reach more than 5 times that of the iron-based filler. Considering that the bioburden per unit volume is higher in the foam state, the performance of the foamed magnesium-based filler is better than that of the iron-based filler, and its efficiency in treating nitrate-containing wastewater is about 8 to 8.5 times that of the solid iron-based filler.
[0043] (5) The pH range for complete precipitation of magnesium ions into magnesium hydroxide is 9.4 to 12.4. The foamed magnesium composite filler provided by the present invention can avoid the mineralization problem caused by the precipitation of iron ions.
[0044] (6) The foam magnesium composite filler provided by the present invention is a self-foaming porous foam structure with a high surface area, which greatly increases the biofilm-forming position of microorganisms.
[0045] (7) The foamed magnesium composite filler provided by the present invention has physical adsorption, which is more conducive to the utilization of nitrate by microorganisms, thereby increasing the ability of the filler per unit volume to process nitrate.
[0046] (8) The magnesium foam composite filler provided by the present invention does not need to be regenerated. It can be used continuously until the filler is dissolved to a certain extent and then new filler can be added, which can save the operating costs of the sewage treatment equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 Schematic diagram of the structure of the reactor used for the autotrophic denitrification test of the filler. DETAILED DESCRIPTION
[0048] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain this patent in detail and do not limit the scope of protection of the present invention in any way.
[0049] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.
[0050] The reactor used in the autotrophic denitrification test of the foam magnesium composite filler prepared in each embodiment and the filler prepared in each comparative example is as follows: Figure 1 The reactor is a packed column reactor, comprising a reactor body 1 and a three-phase separator 2 arranged on the top of the reactor body 1. The reactor body 1 is a closed organic glass container with an inner diameter of 10 cm and a volume of 5 L. The three-phase separator 2 is used to separate mud and water vapor. A water inlet 3 is arranged at the bottom of the reactor body 1, a water outlet 4 is arranged at the top of the reactor, and a reflux inlet 6, a sampling port 5 and a reflux outlet 7 are arranged on the side wall of the reactor body 1 in sequence from bottom to top.
[0051] In each embodiment and comparative example of the present invention, the nitrate nitrogen concentration is tested by ion chromatography (HJ / T84-2001).
[0052] In the embodiments and comparative examples of the present invention, the particle size of the magnesium powder used is 50-200 μm, the particle size of the sodium bicarbonate, calcium carbonate, sodium carbonate, magnesium carbonate and zinc carbonate is 50-200 μm, and the particle size of the iron powder is 50-200 μm.
[0053] Example 1
[0054] The magnesium powder, calcium carbonate and sodium bicarbonate with a mass ratio of 75:5:20 were fully mixed to obtain a mixture, and the mixture was first pressed into a dense semi-solid state by hot extrusion at a temperature of 100°C and a pressure of 300 MPa for 3 hours; the mixture was then heated to 685°C to decompose the foaming agent to produce gas and generate bubbles inside the mixture, and the mixture was expanded to a density of 1.1 g / cm 3 Afterwards, the mixture was cooled and solidified to room temperature to obtain a foamed magnesium composite filler, which was then cut into square particles with a side length of 10 mm.
[0055] The magnesium foam composite filler prepared in this example is loaded into Figure 1 The autotrophic denitrification test was carried out in the reactor body 1 of the reactor shown. The volume of the filler is about 2 / 3 of the capacity of the reactor body 1. The nitrogen-containing wastewater without organic carbon source was simulated and prepared, and the dissolved oxygen in the wastewater was controlled below 2 mg / L by nitrogen oxygen drive. The sludge that had been domesticated in the laboratory for one year was inoculated on the filler and was domesticated again with the above-mentioned simulated water. After that, the wastewater was pumped into the reactor with a peristaltic pump and operated in a continuous flow mode. The inlet nitrate nitrogen concentration was 50 mg / L, no deoxygenation facilities or processes were set, the temperature was 25°C, the reflux ratio was 5, the dissolved oxygen was lower than 0.3 mg / L, and the control system pH was stable between 7.8 and 8.2; when the hydraulic retention time HRT = 1 to 1.5h, the effluent nitrate nitrogen concentration was measured to be 1.0 to 2.0 mg / L, and the effluent nitrate nitrogen removal rate was 97%. The reactor was operated continuously for 2 months, and the effluent water quality was stable. It shows that the autotrophic denitrification process with foam magnesium composite filler as electron donor can remove nitrate nitrogen from sewage.
[0056] Example 2
[0057] The magnesium powder, calcium carbonate and sodium bicarbonate in a mass ratio of 80:10:10 were fully mixed to obtain a mixture, and the mixture was first pressed into a dense semi-solid state by hot extrusion at a temperature of 100°C and a pressure of 300 MPa for 3 hours; the mixture was then heated to 685°C to decompose the foaming agent to produce gas and generate bubbles inside the mixture, and the mixture was expanded to a density of 1.1 g / cm 3 Afterwards, the mixture was cooled and solidified to room temperature to obtain a foamed magnesium composite filler, which was then cut into square particles with a side length of 10 mm.
[0058] The magnesium foam composite filler prepared in this example is loaded into Figure 1 An autotrophic denitrification test was conducted in the reactor body 1 of the reactor shown, and the inlet water concentration and operating parameters were the same as those in Example 1. When the hydraulic retention time HRT = 1 to 1.5 h, the nitrate nitrogen concentration in the effluent was measured to be 1.5 to 2.5 mg / L, and the nitrate nitrogen removal rate in the effluent was 96%. The reactor was operated continuously for 2 months, and the effluent water quality was stable.
[0059] Example 3
[0060] The magnesium powder and sodium bicarbonate with a mass ratio of 80:20 were fully mixed to obtain a mixture, and the mixture was first pressed into a dense semi-solid state by hot extrusion at a temperature of 100°C and a pressure of 300 MPa for 3 hours; the mixture was then heated to 685°C to decompose the foaming agent to produce gas and generate bubbles inside the mixture, and the mixture was expanded to a density of 1.1 g / cm 3 Afterwards, the mixture was cooled and solidified to room temperature to obtain a foamed magnesium composite filler, which was then cut into square particles with a side length of 10 mm.
[0061] The magnesium foam composite filler prepared in this example is loaded into Figure 1 An autotrophic denitrification test was carried out in the reactor body 1 of the reactor shown, and the inlet water concentration and operating parameters were the same as those in Example 1. When HRT = 1-1.5h, the nitrate nitrogen concentration of the effluent was measured to be 4.0-6.0mg / L, and the nitrate nitrogen removal rate of the effluent was 90%. The reactor was operated continuously for 30 days, and the effluent water quality was stable. After 30 days, the treatment effect gradually deteriorated, and the system's stable operation ability was worse than that of the foamed magnesium composite filler prepared in Example 2.
[0062] Example 4
[0063] The preparation method of the foamed magnesium composite filler refers to Example 1, and the only difference from Example 1 is that calcium carbonate is replaced by magnesium carbonate.
[0064] The magnesium foam composite filler prepared in this example is loaded into Figure 1 An autotrophic denitrification test was conducted in the reactor body 1 of the reactor shown, and the inlet water concentration and operating parameters were the same as those in Example 1. When the hydraulic retention time HRT = 1 to 1.5 h, the nitrate nitrogen concentration in the effluent was measured to be 1.5 to 2.5 mg / L, and the nitrate nitrogen removal rate in the effluent was 96%. The reactor was operated continuously for 2 months, and the effluent water quality was stable.
[0065] Example 5
[0066] The preparation method of the foamed magnesium composite filler refers to Example 1, and the only difference from Example 1 is that calcium carbonate is replaced by zinc carbonate.
[0067] The magnesium foam composite filler prepared in this example is loaded into Figure 1 An autotrophic denitrification test was conducted in the reactor body 1 of the reactor, and the inlet water concentration and operating parameters were the same as those in Example 1. When the hydraulic retention time HRT = 1 to 1.5 h, the nitrate nitrogen concentration in the effluent was measured to be 1.2 to 3.8 mg / L, and the nitrate nitrogen removal rate in the effluent was 94%. The reactor was operated continuously for 2 months, and the effluent water quality was stable.
[0068] Comparative Example 1
[0069] The preparation method of the filler refers to Example 1, and the only difference from Example 1 is that the raw materials are replaced by magnesium powder and sodium carbonate in a mass ratio of 75:25 from magnesium powder, calcium carbonate and sodium bicarbonate in a mass ratio of 75:5:20.
[0070] Put the prepared filler into Figure 1 An autotrophic denitrification test was carried out in the reactor body 1 of the reactor shown, and the inlet water concentration and operating parameters were the same as those in Example 1. When the hydraulic retention time HRT = 1-1.5h, the nitrate nitrogen concentration in the effluent was 4-8mg / L, and the nitrate nitrogen removal rate in the effluent was significantly lower than that in Example 1. The reason for this may be that the metal magnesium did not foam, the autotrophic denitrification bacteria were not easy to attach to the surface of the metal filler, and the surface area of the metal magnesium was low, making it difficult for microorganisms to utilize it.
[0071] Comparative Example 2
[0072] The preparation method of the filler is similar to that of Example 1, and the only difference from Example 1 is that the raw materials are replaced by zero-valent iron powder, calcium carbonate and sodium bicarbonate in a mass ratio of 75:5:20 instead of magnesium powder, calcium carbonate and sodium bicarbonate in a mass ratio of 75:5:20. Since zero-valent iron cannot be molten at the operating temperature, the prepared filler is a non-foamed block compacted filler.
[0073] Put the prepared filler into Figure 1 An autotrophic denitrification test was carried out in the reactor body 1 of the reactor shown, and the inlet water concentration and operating parameters were the same as those in Example 1. After the device was debugged and stabilized, the test was run for 20 days. When the hydraulic retention time HRT = 1-1.5h, before the 10th day, the nitrate nitrogen concentration in the reactor outlet water was 12-16mg / L, which was much lower than the foam zinc composite filler in Example 1; on the 10th to 15th day, the nitrate nitrogen concentration in the reactor outlet water increased to about 20mg / L, and brown-red trivalent iron precipitation was observed on the surface of the zero-valent iron. Analysis shows that the reason for the increase in the nitrate nitrogen concentration in the outlet water after 10 days is that trivalent iron is precipitated on the surface of the filler, affecting the utilization efficiency of the filler.
[0074] Comparative Example 3
[0075] The auto-oxygen denitrification test was carried out using zero-valent active iron with a particle size of 2 to 3 mm as filler, and the inlet water concentration and operating parameters were the same as those in Example 1. After the device was debugged and stabilized, the test was run for 20 days. When the hydraulic retention time was 4.5 to 6.0 h, before the 10th day, the nitrate nitrogen concentration of the reactor outlet water was 2.2 to 4.5 mg / L, and the nitrate nitrogen removal rate was equivalent to that in Example 1; from the 10th to the 15th day, the nitrate nitrogen concentration of the reactor outlet water increased from about 4.0 mg / L to 10 mg / L, and brown-red trivalent iron precipitation was observed on the surface of the zero-valent iron. It was analyzed that the reason for the increase in the outlet water concentration was that the trivalent iron was precipitated on the surface of the filler, affecting the utilization efficiency of the filler.
[0076] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A foam magnesium composite filler, characterized in that: The foamed magnesium composite filler comprises magnesium, foaming agent residue and an optional inorganic carbon source and has a porous foam structure.
2. The foamed magnesium composite filler according to claim 1, characterized in that: The density of the foam magnesium composite filler is 0.8-1.2 g / cm 3 .
3. The foamed magnesium composite filler according to claim 1 or 2, characterized in that: The mass ratio of the magnesium, the foaming agent residue and the inorganic carbon source is (70-80): (6.5-13): (0-15).
4. The foamed magnesium composite filler according to any one of claims 1 to 3, characterized in that: The foaming agent residue includes sodium carbonate; And / or, the inorganic carbon source includes at least one of sodium carbonate, calcium carbonate, magnesium carbonate, zinc carbonate, and ferrous carbonate.
5. The method for preparing the foamed magnesium composite filler according to any one of claims 1 to 4, characterized in that: include: The magnesium powder, the foaming agent and the optional inorganic carbon source raw material are mixed to obtain a mixture, the mixture is first pressed by hot extrusion, then heated to decompose the foaming agent to generate gas to expand the mixture, and then cooled and solidified to obtain the foamed magnesium composite filler.
6. The preparation method according to claim 5, characterized in that: include: The mass ratio of the magnesium powder, the foaming agent and the inorganic carbon source raw material is (70-80): (10-20): (0-15); And / or, the foaming agent is sodium bicarbonate; And / or, the inorganic carbon source raw material includes at least one of sodium carbonate, calcium carbonate, magnesium carbonate, zinc carbonate and ferrous carbonate.
7. The preparation method according to claim 5 or 6, characterized in that: The hot extrusion temperature is 90-120°C, the pressure is 270-350Mpa, and the holding time is 2-5 hours; And / or, the heating temperature is 680-690°C; And / or, the preparation method further comprises: cutting the prepared foamed magnesium composite filler into particles, preferably particles with a particle size of 8 to 13 mm.
8. An autotrophic denitrification reactor, characterized in that: The invention comprises the foamed magnesium composite filler described in any one of claims 1 to 4 or the foamed magnesium composite filler prepared by the preparation method described in any one of claims 5 to 7.
9. The reactor according to claim 8, characterized in that The foamed magnesium composite filler accounts for 45-70% of the volume of the reactor.
10. Use of the foamed magnesium composite filler according to any one of claims 1 to 4, or the foamed magnesium composite filler prepared by the preparation method according to any one of claims 5 to 7, or the reactor according to claim 8 or 9 in sewage treatment; especially in treating sewage with a dissolved oxygen concentration of 0.5 to 2.0 mg / L and a ratio of COD concentration to nitrate nitrogen concentration of less than 3.
Citation Information
Patent Citations
Simultaneous phosphorus and nitrogen removal light material, preparation method and application thereof
CN110078221A
Synchronous denitrification and phosphorus removal composite filler and preparation method and application thereof
CN110683631A
Denitrification material based on sulfur autotrophic denitrification, preparation method and application
CN113044974A
Sulfur autotrophic denitrification nitrogen removal slow-release composite filler as well as preparation method and application thereof
CN115925111A